Skin epigenetics: how chromatin regulators orchestrate skin functions - Botchkarev, Vladimir (Henry Stewart Talks, 2014)
Skin structure, functions and development, Molecular control of cell differentiation, What is epigenetics?, What controls variability of skin phenotypes?, Genes encoding keratinocyte-specific proteins, Molecular signature of epidermal layers, Levels of epigenetic regulation, DNA methylation and hydroxymethylation, DNA methylation influence on the epidermis, Post-translational histone/covalent modifications, Histone acetylation/de-acetylation, Polycomb-repressive complex, Polycomb and Trithorax play antagonistic roles, ATP-dependent chromatin remodeling, Non-coding RNA-dependent mechanisms, Nucleus: storage, replication of genetic material, Topological gene interactomes, Morphogenesis of the epidermis, Epidermal differentiation complex, EDC and Lor relocation to nuclear interior, p63 and Brg1 ablation results in retention of EDC, Genome organizer AT-rich binding Satb1 protein, Transcription factor and epigenetic mechanisms, Future directions of epigenetic research